1979
DOI: 10.1111/j.1348-0421.1979.tb00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocinogeny and Antibiotic Resistance of Naturally Occurring Strains of Streptococcus mutans

Abstract: We studied bacteriocinogenies and antibiotic resistances of naturally occurring strains of Streptococcus mutans isolated from different sources.It was found that naturally occurring strains from humans and rats were distinguished by their bacteriocin susceptibilities and production.We had a few incidences of tetracycline resistant strains only among those isolated from rats.It is quite interesting that none of the resistant strains we collected produced bacteriocins.Streptococcus mutans is well known for its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Considering the variadons expected for a study of this type, the MIC were found to be very similar to those observed by other authors (1, 3, 7). No strains requiring high concentrations of antibiotics to achieve inhibition were detected, as has previously been indicated in other studies, particularly in reference to tetracycline (6). Excluding the behavior of several strains to spiramycin and acetyl spiramycin, the remaining antibiotics tested in this study inhibit 100%) of the strains at a concentration of < 2 /ig/ml.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Considering the variadons expected for a study of this type, the MIC were found to be very similar to those observed by other authors (1, 3, 7). No strains requiring high concentrations of antibiotics to achieve inhibition were detected, as has previously been indicated in other studies, particularly in reference to tetracycline (6). Excluding the behavior of several strains to spiramycin and acetyl spiramycin, the remaining antibiotics tested in this study inhibit 100%) of the strains at a concentration of < 2 /ig/ml.…”
Section: Discussionsupporting
confidence: 73%
“…Differences in suscepdbility have been reported to exist between different serotypes (7), which would imply that anatomic and physiological factors exist at the cell wall level. Certain cases of resistance to tetracycline seem to be caused by transposons (5,6). The aim of this study was to examine the evolution of sensidvity in S. tnutans and S. sobrinus over a 5-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of 17 human strains and 7 of 16 rat strains of S. mutans, all of which are nonlysogenic, produce mutacins. Most of the nonmutacinogenic rat strains are tetracycline resistant (290).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The only information available on the mechanism of action of bacteriocins of streptococci indicates an inhibition of DNA, RNA, and protein synthesis (512). No involvement of a plasmid in mutacinogeny has been reported, although extensive surveys have been made (102,225,226,290,294).…”
Section: Downloaded Frommentioning
confidence: 99%